1999
DOI: 10.2307/2656779
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in Nuphar (Nymphaeaceae): evidence from morphology, chloroplast DNA, and nuclear ribosomal DNA

Abstract: The genus Nuphar consists of yellow-flowered waterlilies and is widely distributed in north-temperate bodies of water. Despite regular taxonomic evaluation of these plants, no explicit phylogenetic hypotheses have been proposed for the genus. We investigated phylogenetic relationships in Nuphar using morphology and sequences of the chloroplast gene matK and of the internal transcribed spacer (ITS) regions of nuclear ribosomal DNA. Two major lineages within Nuphar are consistently resolved with the morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 27 publications
4
28
0
1
Order By: Relevance
“…Mit Hilfe von morphologischen und molekularen Methoden wird diese allmählich entschlüsselt (Padgett 1998(Padgett , 1999Padgett et al 1998Padgett et al , 1999. Das Entstehen von Hybriden von N. pumila und N. lutea (N. x intermedia Lebed.)…”
Section: Diskussionunclassified
“…Mit Hilfe von morphologischen und molekularen Methoden wird diese allmählich entschlüsselt (Padgett 1998(Padgett , 1999Padgett et al 1998Padgett et al , 1999. Das Entstehen von Hybriden von N. pumila und N. lutea (N. x intermedia Lebed.)…”
Section: Diskussionunclassified
“…The genus Nuphar (Nymphaeaceae), with its 10-15 species, is a conspicuous component of the freshwater flora throughout most of the Northern Hemisphere (Padgett 1998(Padgett , 2007Padgett et al 1999;Preston and Croft 2001). The least water-lily (N. pumila (TIMM.)…”
Section: Study Speciesmentioning
confidence: 99%
“…N. pumila shares a common ancestor with the widespread lowland species Nuphar lutea, and both taxa form a fertile hybrid, named Nuphar 9 spenneriana Gaudin (Padgett et al 1999;Roweck and Reinöhl 1986;Roweck 1988), that usually occurs in areas where the distributions of both parental species overlap (Heslop-Harrison 1953, 1955. The hybrid Nuphar 9 intermedia is diploid and has the same chromosome number (2n = 34) as both parental species and all other Nuphar spp.…”
Section: Introductionmentioning
confidence: 99%
“…A phylogenetic study carried out on the genus Nuphar (Nymphaeaceae) has shown fruit characters to be informative where floral and the fruit characters supported the geographic grouping of species (Padgett et al, 1999). During the present study, fruit characters were not included as data were not coded for all individuals.…”
Section: Discussionmentioning
confidence: 99%